On Generalized Flatness and Generalized SF-Rings - Abdul-Jabbar, Abdullah M. (Sulaimani Journal for Pure and Applied Sciences, 2015)
The concept of generalized flatness and generalized SF-rings were first introduced by the author in 2007. Now, in the present paper we continue to study generalized flatness, generalized SF-rings and determine more properties of them. Moreover, several results are proved. Finally, compare them with regular rings, left non-singular, strongly regular, strongly π-regular, π-biregular and sπ-weakly regular rings under some conditions.
Keywords: SFrings generalized SFrings generalized flatness regular rings